LaCoxFe1‐xO3‐δ‐QDs/CNTs Composite as an Efficient Electrocatalyst for Oxygen Evolution Reaction. Issue 23 (7th November 2022) - Yang, Haidong; Wang, Qianyi; Ren, Jiajia; Chang, Shan; Zhang, Yongfeng
Abstract: Oxygen evolution reaction (OER) is a critical half‐reaction in the process of electrochemical water splitting, which has been researched a lot in last few years. Nevertheless, OER has high overpotential and sluggish reaction kinetics. Therefore, preparing non‐noble metal catalysts with high surface activity to decrease the activation energy of the reaction is the key to solving these problems. Herein, we report a facile development of an electrocatalyst for OER. The composites of perovskite oxide quantum dots with abundant oxygen vacancies attached to oxidized carbon nanotubes (LaCox Fe1‐x O3‐δ ‐QDs/CNTs) were manufactured by sodium borohydride reduction method. The results evidence that the optimized LaCo0.5 Fe0.5 O2.603 ‐QDs/CNTs sample exhibits optimal electrocatalytic performance (with an overpotential of 210 mV at 10 mA/cm 2 ) and prominent stability towards OER. It should attribute to quantum dots structure, suitable Co/Fe ratio, fitting calcination temperature, appropriate oxygen vacancy concentration. This work will offer novel inspiration for the research and evolution of non‐precious metal catalysts with improved performance. Abstract : Perovskite Oxide Quantum Dots for OER : The superior OER performance of the composites of LaCox Fe1‐x O3‐δ ‐QDs/CNTs is owing to the quantum dots structure and appropriate oxygen vacancy concentration, which can supply even more effective active sites and adsorption‐desorption sites.